Lasting Effects of Workplace Strength Training for Neck/Shoulder/Arm Pain among Laboratory Technicians: Natural Experiment with 3-Year Follow-Up. (10th March 2014) - Mortensen, Peter; Larsen, Anders I.; Zebis, Mette K.; Pedersen, Mogens T.; Sjøgaard, Gisela; Andersen, Lars L.
Abstract : Objectives . This study investigated long-term effects and implementation processes of workplace strength training for musculoskeletal disorders. Methods . 333 and 140 laboratory technicians from private and public sector companies, respectively, replied to a 3-year follow-up questionnaire subsequent to a 1-year randomized controlled trial (RCT) with high-intensity strength training for prevention and treatment of neck, shoulder, and arm pain. Being a natural experiment, the two participating companies implemented and modified the initial training program in different ways during the subsequent 2 years after the RCT. Results . At 3-year follow-up the pain reduction in neck, shoulder, elbow, and wrist achieved during the first year was largely maintained at both companies. However, the private sector company was rated significantly better than the public sector company in (1) training adherence, (2) training culture, that is, relatively more employees trained at the workplace and with colleagues, (3) self-reported health changes, and (4) prevention of neck and wrist pain development among initially pain-free employees. Conclusions . This natural experiment shows that strength training can be implemented successfully at different companies during working hours on a long-term basis with lasting effects on pain in neck, shoulder, and arm.